String tension effects on tennis ball rebound speed and accuracy during playing conditions - Bower, R.; Cross, R. (Journal of Sports Sciences, 2005)
The primary aim of this study was to determine whether variations in rebound speed and accuracy of a tennis ball could be detected during game-simulated conditions when using three rackets strung with three string tensions. Tennis balls were projected from a ball machine towards participants who attempted to stroke the ball cross-court into the opposing singles court. The rebound speed of each impact was measured using a radar gun located behind the baseline of the court. An observer also recorded the number of balls landing in, long, wide and in the net. It was found that rebound speeds for males (110.1±10.2km·h-1; mean±s) were slightly higher than those of females (103.6±8.6km·h-1; P<0.05) and that low string tensions (180N) produced greater rebound speeds (108.1±9.9km·h-1) than high string tensions (280N, 105.3±9.6km·h-1; P<0.05). This finding is in line with laboratory results and theoretical predictions of other researchers. With respect to accuracy, the type of error made was significantly influenced by the string tension (P<0.05). This was particularly evident when considering whether the ball travelled long or landed in the net. High string tension was more likely to result in a net error, whereas low string tension was more likely to result in the ball travelling long. It was concluded that both gender and the string tension influence the speed and accuracy of the tennis ball.